Quality in practical studies through systematic collaboration between field of practice and university.: Experiences from a development project in the social education at Nord University - Sætertrø, Odil; Solum Myren, Gunn Eva (Nordisk Tidsskrift for Helseforskning, 2022)
The purpose of the article is to describe experiences from testing a new practice model in the social education at Nord University in the period 2016-18. The aim of the model was to develop a closer collaboration between education and the field of practice to ensure good quality of the practice period Method: Action research was used as an approach to develop the model. The evaluation was carried out by using focus group interviews with students from the 1st and 2nd year of study and their practice supervisors. Result: Organization and framework can enable interaction between the field of practice and the educational institution. Security in the learning process is created through students in pairs and regular practice supervisors. Conclusion: A multi-year management-based contract that clarifies meeting points between the parts can be central to continuity in the collaboration. Meeting points for mutual exchange of information, development of a common understanding of competence requirements can contribute to ensuring a systematic collaboration. Structured supervision process can provide good conditions for learning in the practical study. Students in pairs and supervision contracts can be important in order to ensure quality in the internship.